Entomopathogenic fungus, Lecanicillium lecanii R. Z are & W. Gams anchored into MCM-41: A new and effective bio-insecticide against Brevicoryne brassicae (Linnaeus, 1758) (Hom: Aphididae) to protect cabbages - Asmar SOLEYMANZADE; Fereshteh KHORRAMI; Hana BATMANI; Khadijeh OJAGHI AGHBASH; Youbert GHOSTA (Acta Agriculturae Slovenica)
Brevicoryne brassicae is a significant pest of cultivated cabbages and vegetable crops in the world. The present study was carried out to examine a potential strategy to enhance the insecticidal activity of Lecanicillium lecanii for cost-effective management of B. brassicae. The insecticidal efficacy of pure entomopathogenic fungus (PEF) and MCM-41 (Mobil Composition of Matter) L. lecanii were assessed against the cabbage aphid under laboratory and greenhouse conditions. The fungus was supported on MCM-41 and was completely characterized by Scanning Electron Microscope (SEM), thermogravimetric analysis (TGA) and Fourier transform infrared (FT-IR) techniques. LC50 values of PEF and MCM-41@fungus were 1.9×106 and 2.5×104 and 2.0×107 and 2.0×105 conidia/ml on adults of B. brassicae under laboratory and greenhouse conditions, respectively. Bioassays demonstrated that MCM-41@fungus significantly decreased LC50 values of entomopathogenic fungus and it was more toxic than L. lecanii at adult stage of the pest. The results showed that pure L. lecanii and its nano-formulation could play key roles as bio-pesticides in B. brassicae management programs.